Die Rechnungsstellung im schweizerischen Obligationenrecht - Bittel, Emanuel (sui generis Verlag, 2020)
Although invoicing is of great importance in practice, there is no fundamental treatment of its effects in the area of ​​application of the Code of Obligations in the Swiss civil law literature. The present study entitled "Invoicing in the Swiss Code of Obligations" aims to close this gap. In it, the author primarily discusses the consequences of invoicing for the origin, scope, due date and limitation of claims and how the invoicing affects the default of the debtor. The thesis is also devoted to the legal consequences of additional declarations by the biller, which are frequently encountered in practice, and sheds light on the legal status of the recipient of the bill.